2020
DOI: 10.1002/eat.23363
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of heat in the phases of the light–dark cycle in the activity‐based anorexia model

Abstract: Background: This research builds on the studies on ambient temperature as a key influence in the recovery of rodents exposed to the activity-based anorexia (ABA) model. The ABA model is an experimental paradigm in which rodents under a restricted feeding schedule and with free access to an activity wheel show signs that parallel those of anorexia nervosa in humans. Objective: The present study focuses on the effects of applying heat during the different phases of the dark-light cycle in the activity levels, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In addition, it is well-established that ABA-induced hyperactivity is an adaptative behavioral response to compensate for hypothermia ( 9 ). Our data are in line with previous studies reporting the beneficial effect of increased ambient temperature to 32°C on the recovery of rats subjected to the ABA model, even after 20% weight loss has occurred ( 10 13 , 15 , 58 ). Although our data confirm former evidence, the use of temperature recording by telemetry allows a constant monitoring of the body temperature throughout the experiment, which constitutes a big advantage when compared to previous reports.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it is well-established that ABA-induced hyperactivity is an adaptative behavioral response to compensate for hypothermia ( 9 ). Our data are in line with previous studies reporting the beneficial effect of increased ambient temperature to 32°C on the recovery of rats subjected to the ABA model, even after 20% weight loss has occurred ( 10 13 , 15 , 58 ). Although our data confirm former evidence, the use of temperature recording by telemetry allows a constant monitoring of the body temperature throughout the experiment, which constitutes a big advantage when compared to previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…AN-associated hyperactivity has been proposed as an adaptative behavioral response to compensate for hypothermia (9). Previous research has shown that exposure to a high ambient temperature (AT) prevents and reverses the hyperactivity and improves feeding patterns, allowing body weight recovery in both male and female rats under ABA conditions (10)(11)(12)(13)(14)(15). These beneficial effects of temperature have been also found in the semi-starvation induced hyperactivity model (SIH) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Using a well-established rodent model, the activity-based anorexia model (ABA), it has been demonstrated that providing heat to the "anorexic" ABA-rodent reduces activity and weight loss (Routtenberg and Kuznesof, 1967;Epling and Pierce, 1996;Hillebrand et al, 2005;Gutierrez et al, 2006;Vazquez et al, 2006;Roura et al, 2020).…”
Section: Ans and Hyperactivitymentioning
confidence: 99%
“…Drug therapies designed to antagonize MC receptors could be combined with a temperature adjustment. It is well known that a continuous warming is beneficial to ABA animals [169] and that rising temperature from 21 to 32 °C can block ABA induction and reduces its related behavior by increasing food intake and reducing RWA [170][171][172]. In this context, a parallelism between the ABA model and AN patients should be evidenced: in fact, warming at 32 °C also showed a fivefold reduction in corticosterone levels in ABA rats if compared to a 21 °C housing [173], and this anxiolytic effect was also present in AN patients when exposed to a heated environment [174].…”
Section: Melanocortinsmentioning
confidence: 99%